CARCINOGENIC AND ORGANO TOXIC COMPOUNDS IN MILK - Wardhan, Rashmi (LIFE: International Journal of Health and Life-Sciences, 2016)
Milk Adulteration has been a serious health issue since the last few decades because of increasing population, industrialization and urbanization of cities like Delhi. Milk is a major diet component for every individual, from infant to adult. Consumption of adulterated milk may cause serious developmental disorders in children. The aim of the present study is to analyse various toxic substance in milk samples collected from different zones of Delhi Capital Region by GC-MS. We observed 41 toxic compounds with varied degree of toxicity like Benzene and related compounds, phthalates and plasticizers, pesticide degradative products and Savoring agents in the samples. These compounds are reported to have ecotoxic, carcinogenic, mutagenic and organotoxic properties. The presence of such toxic substances may not show immediate effects but might cause a serious threat later in the life.